QUALITY ISSUES OF FOREIGN LANGUAGE TEACHING USING ARTIFICIALINTELLIGENCE IN THE PROCESS OF IMPLEMENTING DIGITALTECHNOLOGIES IN MODERN EDUCATION (Universal International Scientific Journal, 2026)
This article examines the challenges and opportunities of using artificial intelligence (AI) inforeign language teaching within the context of implementing digital technologies in moderneducation. The study analyzes how AI-based learning platforms can enhance students’ engagement,individualize the learning process, and improve the quality of language acquisition. Specialattention is given to the pedagogical potential of AI tools, such as speech recognition, interactiveexercises, automated feedback, and adaptive learning paths. The research also identifies key issues,including teachers’ digital competence, methodological support, and cognitive overload caused byexcessive information. The findings demonstrate that methodically grounded and pedagogicallyguided use of AI in language education significantly contributes to the effectiveness and quality oflearning outcomes.
Keywords: artificial intelligence; digital education; foreign language teaching